Impact of Biosynthesized Zinc Oxide Nanoparticles on the Kidneys Tissues of Male Mice Experimentally Infected with Entamoeba histolytica - Laith A. Yaaqoob; Mohannad Hamid Jasim; Lima Tariq Youash Lazar; Saade Abdalkareem Jasim; Thaer Abdulqader Salih (Acta Biologica Slovenica, 2025)
Entamoeba histolytica has been detected in stool samples of patients attending the Children’s General Hospital in Kirkuk City. Zinc oxide nanoparticles (ZnO NPs) are biosynthesized by Pseudomonas aeruginosa, which produces the pigment pyocyanin that acts as an agent of reducing in the production of ZnO NPs. The purpose of this work was to ascertain how ZnO NPs might be used therapeutically to treat E. histolytica-infected mice's kidney tissues. Scanning electron microscopy used to characterize biosynthesized ZnO NPs , atomic force microscopy, Fourier transform infrared spectroscopy, UV-visible spectroscopy and X-ray diffraction. ZnO NPs were used to treat mice that had been experimentally infected with E. histolytica. Mouse kidneys were collected and divided into six groups for evaluation. Two groups served as negative and positive controls, respectively. Three other groups (four mice each) were treated with 30, 45, or 60 µg/mL ZnO NPs once daily for ten days. The final group was the uninfected group and treated with 30 µg/mL ZnO NPs. Mice treated with 30, 45, and 60 µg/mL ZnO NPs had kidney histological sections that resembled the negative control, demonstrating that the nanoparticles were effective against the parasite. The uninfected group treated with ZnO NPs showed no negative effects on the kidney tissue.